If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 3x + 14 Reorder the terms: -2 + 12x = 3x + 14 Reorder the terms: -2 + 12x = 14 + 3x Solving -2 + 12x = 14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 12x + -3x = 14 + 3x + -3x Combine like terms: 12x + -3x = 9x -2 + 9x = 14 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 9x = 14 + 0 -2 + 9x = 14 Add '2' to each side of the equation. -2 + 2 + 9x = 14 + 2 Combine like terms: -2 + 2 = 0 0 + 9x = 14 + 2 9x = 14 + 2 Combine like terms: 14 + 2 = 16 9x = 16 Divide each side by '9'. x = 1.777777778 Simplifying x = 1.777777778
| -2n^2+15n-13=0 | | 154=x^2+15x | | -4y-12x=4 | | 2n^2+15n-13=0 | | 0.4*x=75000 | | a-32=29 | | 3x+14=-82 | | 4x^2-50x+486=0 | | t=16t^2+3136 | | X/2-8=6 | | 7.9+d=12 | | 12x-2=-3x+14 | | 2cos^2x+5cosx+5=0 | | -7-5x=-22 | | 6(1-x)+5=2x+3 | | -x-8+7= | | (x-4)(2x+5)= | | (5+3x)-(10x-15)=-22 | | (5+3x)-(10a-15)=-22 | | 26=g | | 6^9-x=1/36 | | 7-3+5x(6-2)= | | 7x^2-4x-6=0 | | h/-1.05=-o.36 | | -48a+8a=-48 | | t=1x+2 | | 4x^2-y^2-48x+140=0 | | 12x^4-8x+4x^2-3= | | 3x+8=8x-13 | | -4(-p-7)-2(5p-4)=12 | | -13m=5(1+4m)-2m | | x^2+y^2+2x+1=0 |